Accessing electronic database for curriculum delivery in schools: implication for school library media specialists (2009)
This paper discussed the role of electronic databases in education with emphasis on the means of accessing the electronic databases. The paper further highlighted the various types and categories of electronic databases which the schools can explore in the process of teaching and learning as well as the techniques of searching. The implication of electronic databases on the role of the School Library Media Centres and School Media Specialists was also discussed. A list of electronic databases that schools can explore for effective teaching and learning were also presented.